Saponins from Panax notoginseng ameliorate steroid resistance in lupus nephritis through regulating lymphocyte-derived exosomes in mice - Chen, Jia; Zhou, Qingyun; Lu, Ying (Frontiers in Pharmacology, 2022)
Steroids have been used as a classical treatment for lupus nephritis (LN) with excellent efficacy. However, long-term steroid therapy can result in the development of steroid resistance; thus, creating a significant limitation for the application of this therapeutic option is vital. In our previous study, we found that Panax notoginseng saponins (PNS) reversed the steroid resistance of lymphocytes in mice with LN, although the mechanisms by which steroid resistance improved kidney function after the improvement of lymphocyte resistance was not elucidated. Recent studies revealed that splenic lymphocyte-derived exosomes are involved in intercellular messaging, the reversal of renal steroid resistance, and the improvement of efficacy while circumventing the toxic side effects of steroid drugs. To validate these findings, a steroid-resistant mouse model of LN was established. We administered model mice with different drug treatment modalities and then extracted splenic lymphocyte-derived exosomes after four weeks of intervention and injected exosomes collected from each group into homologous untreated LN mice. The exosomes were taken up effectively by the kidney. We also investigated whether extracted primary glomerular endothelial cells (GECs) could internalize splenic lymphocyte-derived exosomes. PNS intervention in the lymphocyte-derived exosomes group significantly reduced the expression of multi-drug resistance 1 (MDR1) and P-glycoprotein (P-gp) in mice kidney tissues and GECs, urinary protein level, and serum levels of creatinine, urea nitrogen, Anti-nuclear antibodies (ANA), and Anti-double-stranded DNA (dsDNA). Moreover, there were reductions in renal immune complex deposition and the production of membrane attack complex (MAC). The T-cell-mediated immune-inflammatory response was also inhibited while renal pathology was improved which will potentially be a new tool in the treatment of LN.